Daylight Modelling of a Portuguese Baroque Library - Saraiva, Nuno Garcia (2019)
The XVIII century baroque King John’s Library is one of the most important buildings of the University of Coimbra, which was declared World Heritage patrimony by UNESCO in 2013. As one of the main touristic attractions, it has been object of study on the assessment of the books and furniture conservation. One of the aspects that affect their preservation is the exposure to daylight, which degrades the shelves finishing and the books covers and paper. To prevent the continuous degradation of the patrimony, this work presents a study of the indoor daylight conditions. The software Radiance is used in order to generate accurate annual illuminance maps and detailed daylight indoors images. The results show that natural lighting is a threat to most of the patrimony and must be reduced. This analysis is a contribution to determine an appropriate and comprehensive preservation strategy leaving space to further investigation within this field.